PROSES SEKURITISASI DAN DESEKURITISASI DALAM UPAYA MENURUNKAN ANGKA KASUS COVID-19 DI INDONESIA - Yusa Djuyandi; Hasya Aiman Nadhir; Afifah Amaliya Pohan; Duta Smaradana; Adisa Naura Priadi (P3M STISIPOL Dharma Wacana Metro, 2023)
Over time, there has been a paradigm shift regarding the concept of security itself, where initially aspects that were considered as security issues only revolved around the military and national defense. Not only for Indonesia, but also for the world, Covid-19 has become a security issue or threat to the state, especially the community itself. This research analyzes how the process of securitization and desecuritization in an effort to reduce the number of Covid-19 cases in Indonesia. The method used in this research is a qualitative method, with the data collected from secondary data which includes news, agency reports, books and journal articles on the handling of the Covid-19 pandemic. This study analyzes that the securitization carried out by the government against this outbreak was less successful because of the inappropriate handling since the beginning of this outbreak. The government from the beginning only focused on the economic approach, this made there was no certainty in treating the Covid-19 case as a threat. In addition, this has also caused public trust in the government to decline and communication between government figures and the wider community to be poor due to various mistakes that continue to be made by the government.